2012
DOI: 10.1063/1.4714660
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient accelerator of dense matter using laser-induced cavity pressure acceleration

Abstract: Acceleration of dense matter to high velocities is of high importance for high energy density physics, inertial confinement fusion, or space research. The acceleration schemes employed so far are capable of accelerating dense microprojectiles to velocities approaching 1000 km/s; however, the energetic efficiency of acceleration is low. Here, we propose and demonstrate a highly efficient scheme of acceleration of dense matter in which a projectile placed in a cavity is irradiated by a laser beam introduced into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…In particular, it was shown that the basic, unique feature of the accelerator is extremely high energetic efficiency of acceleration  acc = E p /E L (E p is kinetic energy of the projectile, E L is energy of the laser beam) which for a light (CH) plasma projectile can reach the values even above 50% [2]. Here, we will present exemplary results demonstrating that the hydrodynamic LICPA accelerator can be an efficient tool for generation of high-current-density moderate-energy ion beams as well as acceleration of heavy (~ 10 g) macroparticles.…”
Section: The Hydrodynamic Licpa Acceleratormentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, it was shown that the basic, unique feature of the accelerator is extremely high energetic efficiency of acceleration  acc = E p /E L (E p is kinetic energy of the projectile, E L is energy of the laser beam) which for a light (CH) plasma projectile can reach the values even above 50% [2]. Here, we will present exemplary results demonstrating that the hydrodynamic LICPA accelerator can be an efficient tool for generation of high-current-density moderate-energy ion beams as well as acceleration of heavy (~ 10 g) macroparticles.…”
Section: The Hydrodynamic Licpa Acceleratormentioning
confidence: 99%
“…Main properties of the hydrodynamic LICPA accelerator were investigated experimentally and numerically in [2]. In particular, it was shown that the basic, unique feature of the accelerator is extremely high energetic efficiency of acceleration  acc = E p /E L (E p is kinetic energy of the projectile, E L is energy of the laser beam) which for a light (CH) plasma projectile can reach the values even above 50% [2].…”
Section: The Hydrodynamic Licpa Acceleratormentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38]); • studies of shock wave generation and non-linear interaction of laser with plasma at the conditions relevant to shock ignition (e.g. [39,40]).…”
Section: The Hiper Project and Current Fusion-related Research Of Thementioning
confidence: 99%